2020
DOI: 10.1002/anie.202009575
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Nitrate Regulated Sulfone Electrolytes for Lithium Metal Batteries

Abstract: The electrolytes in lithium metal batteries have to be compatible with both lithium metal anodes and high voltage cathodes,a nd can be regulated by manipulating the solvation structure.H erein, to enhance the electrolyte stability,l ithium nitrate (LiNO 3)a nd 1,1,2,2-tetrafuoroethyl-2',2',2'trifuoroethyl(HFE) are introduced into the high-concentration sulfolane electrolyte to suppress Li dendrite growth and achieve ah igh Coulombic efficiency of > 99 %f or both the Li anode and LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(192 citation statements)
references
References 68 publications
5
187
0
Order By: Relevance
“…The choose of NO 3 − as the SEI enabler of interest in this work was based on two considerations: Firstly, lithium nitrate (LiNO 3 ) has been widely recognized as an outstanding film‐forming reagent for Li protection in different electrolyte systems. The as‐generated uniform and highly ionic conductive SEI contributes to high‐efficiency Li plating/stripping [17–19] . Additionally, NO 3 − is of high Gutmann donor number (DN, 22), which affords distinct cation solvation structure even in dilute electrolyte [20] .…”
Section: Resultsmentioning
confidence: 99%
“…The choose of NO 3 − as the SEI enabler of interest in this work was based on two considerations: Firstly, lithium nitrate (LiNO 3 ) has been widely recognized as an outstanding film‐forming reagent for Li protection in different electrolyte systems. The as‐generated uniform and highly ionic conductive SEI contributes to high‐efficiency Li plating/stripping [17–19] . Additionally, NO 3 − is of high Gutmann donor number (DN, 22), which affords distinct cation solvation structure even in dilute electrolyte [20] .…”
Section: Resultsmentioning
confidence: 99%
“…By using high-resolution transmission electron microscopy (TEM, Figure 7e) and XPS depth profiling (Figure 7f), they confirmed that N-containing species, such as Li additive. 94 By using molecular dynamics (MD) simulations, they pointed out that the NO 3 − anions in the Li + solvation sheath could promote the coordination of TFSI − anions with Li + (Figure 8e). During battery cycling, these anions in the Li + solvation sheath would be reduced and formed an inorganic SEI.…”
Section: Electrolyte Engineeringmentioning
confidence: 99%
“…Numerous researches have been taken to artificially obtain suitable SEI to achieve the uniform Li + deposition by selecting suitable electrolyte additives [24–30] . Previous studies have been proved that the F‐containing electrolyte additive could help to obtain high CE and long stable cycling performance due to the formation of LiF in the SEI film [31–36] . Because the LiF possesses low Li + diffusion barrier and large band gap (13.6 eV), which could facilitate the fast transportation of Li + and block the electrons from passing through SEI for side reaction with electrolyte.…”
Section: Introductionmentioning
confidence: 99%